2010
DOI: 10.1021/jf903416a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Organic and Conventional Growing Conditions on the Nutrient Contents of White Head Cabbage (Brassica oleracea var. capitata) during Two Successive Seasons

Abstract: Organically and conventionally grown white head cabbage (Brassica oleracea var. capitata) plants were cultivated during two successive seasons (spring and autumn) to evaluate the effects of the applications on the nutrient content of the edible part of cabbage plants. Seventeen different organic applications containing farmyard manure (FM), chicken manure (CM), and blood meal (BM) and 1 chemical fertilizer and 1 control, collectively 19 treatments, were examined under the open-field conditions. Recommendations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Of course, many factors can influence the content of vitamin C including growing conditions, growing locations and cultivars, and the findings cannot be generalized (Lee & Kader 2000). Vitamin C levels found in jambu were lower than in other vegetables, such as spinach, grown under either conventional or organic fertilization (Citak & Sonmez 2010).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Of course, many factors can influence the content of vitamin C including growing conditions, growing locations and cultivars, and the findings cannot be generalized (Lee & Kader 2000). Vitamin C levels found in jambu were lower than in other vegetables, such as spinach, grown under either conventional or organic fertilization (Citak & Sonmez 2010).…”
Section: Resultsmentioning
confidence: 93%
“…Several studies have shown that the mode of cultivation influences the content of compounds such as nitrate (Citak & Sonmez 2010), which can range from 1 to 10,000 mg kg −1 (Ximenes et al 2000), and antioxidants (Lima & Vianello 2011). However, contradictory data have been presented (Hoefkens et al 2010;Smith-Spangler et al 2012).…”
mentioning
confidence: 99%
“…It was slightly acidic, so would have slightly countered the effects of the alkaline soil used in the experiment. Poultry manure from other sources can be slightly alkaline, giving a tendency to raise soil pH (Citak and Sonmez, 2010;McGrath et al, 2010), and such manure would be less useful in the soil used in our experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Mantovi et al [36] reported that wheat grain from amended soils showed higher P concentrations than those of plants treated with mineral fertilizers. Citak and Sonmez [38] also noted a greater concentration of nutrients in the edible part of cabbage (Brassica oleracea) when grown in soil amended with organic residues (bovine and chicken manure and blood meal) when compared to vegetables composted with mineral fertilizers.…”
Section: Soil Phosphorus Content In the Long-term Experimentmentioning
confidence: 97%